2014
DOI: 10.2340/00015555-1681
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Remission of Eczema in Children: A Population-based Follow-up Study

Abstract: The aim of this study was to analyse factors associated with remission of atopic dermatitis (AD) in childhood. A population-based AD cohort of 894 children aged 1-3 years from a cross-sectional baseline study in 2000 was followed up in 2005. The association between remission, background, health, lifestyle, and environmental variables was estimated with crude and multivariable logistic regression. At follow-up, 52% of the children had remission. Independent factors at baseline predicting remission were: milder … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 53 publications
0
31
0
2
Order By: Relevance
“…6,23,28,31,44,45,48 The duration of AD persistence was significantly higher in females (median: 9.0 years; mean ± SE: 12.7 ± 0.2 years) compared with males (median: 7.0 years; mean±SE: 11.7 ± 0.2 years) (HR 1.15; 95% CI 1.04-1.27; P = .006) (Fig 2, E).…”
Section: Ad Persistence By Gendermentioning
confidence: 90%
See 2 more Smart Citations
“…6,23,28,31,44,45,48 The duration of AD persistence was significantly higher in females (median: 9.0 years; mean ± SE: 12.7 ± 0.2 years) compared with males (median: 7.0 years; mean±SE: 11.7 ± 0.2 years) (HR 1.15; 95% CI 1.04-1.27; P = .006) (Fig 2, E).…”
Section: Ad Persistence By Gendermentioning
confidence: 90%
“…After review of the titles and abstracts, 9326 were excluded; an additional 634 articles were excluded after full-text review. In total, 46 studies were included in the review, of which 44 had valid frequency data that could be pooled, 7 had valid data to assess the effects of gender, 6,23,28,31,44,45,48 6 for allergen sensitization, 6,17,23,36,40,45 and 3 for baseline AD severity 17,28,40 on disease persistence. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) flow diagram is presented in Fig 1. …”
Section: Literature Searchmentioning
confidence: 99%
See 1 more Smart Citation
“…They reported that remission was achieved in 52% of children. The authors also reported mild AD, older onset age, no eruption on flexion sides, no food allergies, and living in suburban areas as factors of high remission rate …”
Section: Cq18 Can Remission Of Ad Be Expected With Age?mentioning
confidence: 81%
“…Most of the AD patients are diagnosed before childhood especially in the first year of life2627. One questionnaire-based survey of 7~8 years old Korean children reported the following findings: onset age: <2 years in 43.7% and ≥5 years in 26% of children21.…”
Section: Discussionmentioning
confidence: 99%